Pengaruh latihan skipping dan squat jump terhadap kemampuan smash permainan bulutangkis - Anugrah, Reski; Santos, Maria Herlinda Dos; Bahar, Umrah; Mutmainna, Andi; Ilahi, Rahmat; Rijaluddin, Khalid (Universitas Hamzanwadi, 2023)
This study aims to determine how the effect of skipping and squat jump training on smash ability in badminton games for male students of SMA Negeri 1 Kodeoha Extracurricular. Experimental research method using the static group pretest-posttest design. The population in the study amounted to 45 students with a research sample of 30 students. Data collection will be held twice the test, namely before being given treatment and after being given the final treatment. The results of data analysis and hypothesis testing were obtained using SPSS 20. The results of the analysis showed that there was a significant effect of skipping training on the ability to smash the game, indicated by the t value of tcount 5.527 > ttable 2.145 and p value (0.000) < 0.05. (2). There is a significant effect of squat jump training on badminton smash ability, indicated by the value of tcount 2.291 > ttable 2.145 and the results of p value (0.038) < 0.05. (3). Skipping training is more effective than squat jump on smash ability in badminton games indicated by the value of tcount 2.237 > ttable 2.048 and p value (0.033) > from 0.05. Based on the results of the analysis and discussion that has been described, it can be concluded that skipping and squat jump training have an effect on smash ability in badminton games for male extracurricular students of SMA Negeri 1 Kodeoha.